Biofiltration on organic media, a new sustainable technology for wastewater treatment in small communities and industries - Marco A. Garzón Zúñiga; Gerardo Buelna; Gabriela E. Moeller Chávez (Tecnología y ciencias del agua, 2012)
The large amounts of organic matter, nutrients, heavy metals and other chemical substances in water is one of the most troubling problems faced by all countries worldwide. Therefore, the priorities for sustainable development are the control, reduction and treatment of wastewater from urban, agricultural, agro-industrial and industrial discharges into water bodies. Unfortunately, the operational complexity and high investment and maintenance costs associated with conventional wastewater treatment systems have limited their usage in small municipalities, rural zones and small and medium industries. The biofiltration process on organic medium has recently been developed in Canada in order to solve the sanitation problems and meet its needs in these important sectors. This process is based on the capacity of certain organic media to act as natural resins, which are able to retain different types of pollutants through adsorption/absorption mechanisms and contribute to the settling of microorganisms capable of degrading the entrapped pollutants. Because this technology is decentralized and can resolve problems in many rural and semi-urban zones, it has recently been of interest in Mexico. It has been tested in the laboratory for treating urban and industrial wastewater using organic materials in the region and the first realscale system has been installed. Therefore, the objective of this research is to present the main results obtained for this technology at the real-scale and its impact on the urban sectors (small municipalities and rural zones) and agro-industry (pig and poultry farms) in Canada and Mexico.